Eradication of Growth of HER2-Positive Ovarian Cancer With Trastuzumab-DM1, an Antibody-Cytotoxic Drug Conjugate in Mouse Xenograft Model. Issue 7 (1st September 2014) - Yu, Lin; Wang, Yuxi; Yao, Yuqin; Li, Wenting; Lai, Qinhuai; Li, Jun; Zhou, Yongjun; Kang, Tairan; Xie, Yongmei; Wu, Yangping; Chen, Xiangzhen; Yi, Cheng; et al.
Abstract : Objective: Ovarian cancer is 1 kind of a highly malignant gynecologic tumor, and current treatments have not achieved satisfactory effects. Human epidermal growth factor receptor 2 (HER2)–targeted therapies including trastuzumab and trastuzumab-DM1 (T-DM1) (antibody-cytotoxic drug conjugates) have been applied to treat HER2-overexpressing breast cancers in clinic. In the present study, we explored whether T-DM1 could effectively treat HER2-positive human ovarian carcinoma in vitro and in vivo. Methods: HER2 expressions of 6 ovarian cancer cell lines and 2 breast carcinoma cell lines were validated, and the binding capacity of T-DM1 to HER2-positive ovarian cancer SKOV3 cells were analyzed by flow cytometry. Nude mice bearing intraperitoneal and subcutaneous SKOV3 xenografts were used to investigate the antitumor effect of T-DM1. Results: High HER2 expressions in SKOV3 cell lines were detected. The binding capacity of T-DM1 to HER2-positive SKOV3 cells was in a similar manner comparing with trastuzumab. In vitro, T-DM1 showed strong growth inhibitory on SKOV3 cells, with IC50 values of 0.15 nmol/L. Nude mice bearing intraperitoneal and subcutaneous SKOV3 xenografts were used to investigate the antitumor effects of T-DM1 in vivo. In subcutaneous xenografts model, T-DM1 (30 mg/kg and 10 mg/kg) indicated significant anticancer effects. It is noteworthy that tumors were completely eradicated in the T-DM1 (30 mg/kg) group, and no regrowth was observed in a long time after the termination of the treatment. In the peritoneal xenograft model, tumor nodules in 3 of 7 mice were hardly observed in the abdominal cavity of mice after intraperitoneal injection of T-DM1 (30 mg/kg). At the same time, tumor nodules from the other 4 mice weighed on the average of only 0.07 g versus 1.77 g in control group. Conclusions: Our data showed that T-DM1 possessed promising antitumor effects on HER2-overexpressing ovarian cancer in mouse model, which provided valuable references for the future clinical trials.